Iron Men and Tin Fish. - Newpower, Anthony (War, Technology, and History Ser., 2006)
Deals with the torpedo problem, building its case out of original research from the archives of the Bureau of Ordnance, Vice Admiral Lockwood's personal correspondence, and records from the Admiralty in the British National Archives. This work is complemented by correspondence and interviews with men who participated in the events.